Complete viral genome sequence and discovery of novel viruses by deep sequencing of small RNAs: A generic method for diagnosis, discovery and sequencing of viruses - Kreuze, Jan F.; Pérez, A.; Untiveros, M.; Quispe, D.; Fuentes, S.; Barker, I.; Simon, R. (Elsevier, 2009)
We report the first identification of novel viruses, and sequence of an entire viral genome, by a single step of high-throughput parallel sequencing of small RNAs from diseased, as well as symptomless plants. Contigs were assembled from sequenced total siRNA from plants using small sequence assembly software and could positively identify RNA, ssDNA and dsDNA reverse transcribing viruses and in one case spanned the entire genome. The results present a novel approach which cannot only identify known viral pathogens, occurring at extremely low titers, but also novel viruses, without the necessity of any prior knowledge.